2020
DOI: 10.1039/c9sc05766h
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic access to the rare antiarose sugar via an unusual reductase-epimerase

Abstract: Rubrolones, isarubrolones, and rubterolones are recently isolated glycosylated tropolonids with notable biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…16e). 39,40 Although the catalytic mechanism of homologous enzymes has been well elucidated, to our knowledge, it has not been reported that this enzyme can conduct reduction and isomerization on the backbone of type II polyketides. In path B, two enzymes are required to work coordinately in the rst step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16e). 39,40 Although the catalytic mechanism of homologous enzymes has been well elucidated, to our knowledge, it has not been reported that this enzyme can conduct reduction and isomerization on the backbone of type II polyketides. In path B, two enzymes are required to work coordinately in the rst step.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TjhD4 belongs to the NADH-dependent epimerases, which usually participate in deoxysugar biosynthesis and exploit the enol interconversion of α-carbonyl to achieve isomerization (Figure S16e). , Although the catalytic mechanism of homologous enzymes has been well elucidated, to our knowledge, it has not been reported that this enzyme can conduct reduction and isomerization on the backbone of type II polyketides.…”
Section: Discussionmentioning
confidence: 99%
“…The rub BGC consists of 22 open reading frames (ORFs) (Figure 1B), of which 14 (i.e., RubS3-S5, S7, R, E1-E4, E6, E8-E9) have had their role in rubrolone biosynthesis fully characterized. [10,11] In a previous study, we obtained and screened cosmids p9B10 and p10C7 from the genomic library of S. sp. KIB-H033.…”
Section: Heterologous Expression Of Cosmid P10c7 Accumulates Tropolon...mentioning
confidence: 99%
“…The complete rub BGC was expressed in the heterologous host Streptomyces albus J1074, which served as a convenient platform on which to facilitate further in vivo studies [10] . This rub BGC (Figure 1B) contains the seven genes rubS1 ‐ rubS7 , which were attributed to the biosynthesis of the rare antiarose sugar and its subsequent conjugation to the rubrolone aglycones [11] . Sugar‐related gene deletion mutants have been proven to accumulate large amounts of rubrolone aglycone 1 (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…[10] This rub BGC (Figure 1B) contains the seven genes rubS1-rubS7, which were attributed to the biosynthesis of the rare antiarose sugar and its subsequent conjugation to the rubrolone aglycones. [11] Sugar-related gene deletion mutants have been proven to accumulate large amounts of rubrolone aglycone 1 (Figure 1C). The rub BGC also encodes the putative polyketide synthases RubE1-E9, which are presumably responsible for synthesis of the butyryl-CoA starter unit and rubrolone backbone.…”
Section: Introductionmentioning
confidence: 99%